THE EFFECT OF SOCIAL MEDIA USE ON THE WRITING ABILITY OF STUDENTS OF STIEBI PRANA PUTRA LUBUKLINGGU CAMPUS - Sulastri Ningsih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The digital era has transformed student communication patterns through social media platforms, yet its impact on academic writing abilities requires empirical investigation. This study aims to analyze the influence of social media usage on writing abilities of STIEBI Prana Putra Lubuklinggu students. The research employed a quantitative approach with cross-sectional survey design involving 50 Management Study Program students from semesters 3-8. Data were collected through structured online questionnaires and validated writing ability assessment instruments. Data analysis utilized Pearson correlation and multiple regression with SPSS version 25 software. Results revealed significant negative influence of social media usage intensity on academic writing abilities (r=-0.412, p<0.01) with 38.7% variance contribution. Instagram and TikTok platforms negatively correlated with linguistic accuracy, while writing activities on social media showed positive influence on writing creativity. These findings indicate that undirected social media usage may hinder formal writing skill development, yet structured writing activities on digital platforms can support learning. This research provides important contributions for developing writing learning strategies that effectively integrate digital technology.